THE FACTORS OF CAUSE LOW USE OF LONG TERM CONTRACEPTION METHOD IN PUSKESMAS TRUCUK I DISTRICT OF KLATEN - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2018)
Background. Factors influencing the selection of contraceptive methods used were prediction The low utilization of MKJP KB is caused by several factors. Factors influencing the selection of contraceptive methods used were prediction factors (age, education, number of children, knowledge, attitude), supporting factors (availability of contraceptives, house distance to puskesmas, travel time and cost), driving factors (health care support) . Acceptors who choose non-long-term contraceptives mention the reasons for choosing a family planning method because they do not need to show genitals in their installation. Long-term contraceptive methods (MKJPs) are users of intrauterine devices (IUDs) and implants 221,824 (23.74%) and non-users of contraceptive methods long term 712,481 (76.26%) Aim. Knowing what factors cause low use of long-term contraceptives in Trucuk Health Center of Klaten Regency. Research methods. This research uses descriptive method with cross sectional approach. The population in this study were all family planning acceptors of Non Long Term Contraceptive Method (MKJP) in Trucuk I District Health Center of Klaten Regency on January 1 to November 2016, with 1,631 people, 86 samples. Sampling technique purposive sampling. Data analysis using frequency distribution.  Research Result. Factors influencing the selection of contraceptive methods used were prediction factors (age is 46,5%, education is 44,2%, number of children is 65,1%, knowledge is 69,8%), supporting factors is 77,9% (availability of contraceptives, house distance to public health, travel time and cost), driving factors (health care support). Conclusion. The level of knowledge about family planning is sufficient, husband support is good, social culture is not good.